The participation of a juvenile victim’s representative in criminal proceedings: procedural and forensic aspects (Law and Safety, 2024)
The article identifies the procedural and forensic aspects of participation of an attorney-at-law engaged to represent the interests of a juvenile victim in criminal proceedings. Based on the generalization of theoretical developments of Ukrainian scholars, it is found that they prefer to study the problem of protection of rights and legitimate interests of a minor suspect or accused. At the same time, given the current trends in crime, it should be noted that it has a devastating impact on the psyche of children. Moreover, they are increasingly becoming victims of criminal offences, especially those involving violence. This has raised the challenge of ensuring proper protection and the best interests of the minor victim.Based on the results of the scientific research, it has been determined that one of the guarantees of ensuring the procedural interest of a juvenile victim is the principle of competent legal representation. The algorithm for engaging a lawyer from a free legal aid centre to provide legal services to a victim is proposed. The importance of its implementation is emphasised for two reasons: 1) on the grounds that the interests of the child may prevail over the interests of the parents or other legal representative; 2) representatives of the prosecution and the court are obliged to act in accordance with the law, and not to take measures to implement the procedural interest of the minor victim. It is determined that an attorney-at-law, as a professional lawyer, is able to explain the rights of the victim in a language accessible to a minor, to make sure that the legal representative acts in his or her interests, to draw up a civil claim, and to draft a reconciliation agreement. Tactical recommendations for conducting investigative (‘search’) actions and the principles to be followed to ensure that the proceedings are conducted in accordance with international standards are formulated.The significance of the victim’s representative’s participation in investigative (search) actions, as well as at the stages of concluding a plea agreement and familiarisation with the criminal proceedings is pointed out. The article substantiates the expediency of applying the standard of “reliable information and obvious grounds” when deciding on the appointment of a comprehensive psychological and psychiatric examination of a juvenile victim.